Analisis Ketercapaian Kinerja Utama (Important Performance Analysis) City Branding Kota Surakarta di Sektor Pariwisata - Muhammad Anwar Farouqi; Ernady Syaodih Syaodih (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. City branding is an urban marketing strategy that aims to strengthen the relationship between visitors and build a good city image. Unfortunately, branding has made the name Solo more well-known, but has not had enough economic impact. The problem arises how the level of achievement of performance and importance in the development of city branding. The purpose of this study is to find out how city branding is carried out by the Surakarta City government in an effort to increase the potential for visiting tourists. Data analysis methods used include IPA analysis (Importance Performance Analysis) and primary data collection methods (interviews, questionnaires, observations) and secondary (document review). Based on the results of the analysis of the calculation of the government's performance and interests in each indicator, the government is expected to improve tourism branding, technology, and socio-cultural conditions. The conclusion of this research is that most of the government's performance exceeds expectations and the government carries out many programs that facilitate the community. The recommendation for the Surakarta City government is to synergize every program of activities and services in the development of city branding Abstrak.City branding adalah strategi pemasaran perkotaan yang bertujuan untuk memperkuat hubungan antara pengunjung dan membangun citra kota yang baik. Sayangnya, branding telah membuat nama Solo semakin dikenal, namun belum cukup berdampak secara ekonomi. Timbul permasalahan bagaimana tingkat kertecapaian kinerja dan kepentingan dalam pengembangan city branding. Tujuan dari penelitian ini yaitu untuk mengetahui bagaimana city branding yang dilakukan oleh pemerintah Kota Surakarta dalam upaya meningkatkan potensi berkunjung wisatawan. Metode analisis data yang digunakan meliputi Analisis IPA (Importance Performance Analysis) dan metode pengumpulan data primer (wawancara, kuesioner, observasi) dan sekunder (menelaah dokumen). Berdasarkan hasil analisis perhitungan kinerja dan kepentingan pemerintah dalam setiap indikator, pemerintah diharapkan dapat meningkatkan branding wisata, teknologi, dan kondisi sosial budaya. Kesimpulan dari penilitian ini sebagian besar kinerja pemerintah melebihi ekspetasi dari harapan dan pemerintah banyak melakukan program yang memfasilitasi masyarakat. Adapun rekomendasi untuk pemerintah Kota Surakarta yaitu mensinergikan setiap program kegiatan dan pelayanan dalam pengembangan city branding.